Pengamanan Data pada Media Penyimpanan Cloud Menggunakan Teknik Enkripsi dan Secret Sharing - Mohammad Fachry; Ari Kusyanti; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Cloud computing is a technology that used to store data online. With only internet connection, store and access data can be an easy task. However, cloud computing technology also cause some security problems. Cryptography is a study of how data can be secured. Therefore, applying cryptography in cloud computing environment is not a new thing. New algorithms and combination between them is expanded and studied to ensure security aspects such as confidentiality, integrity and availability. In this research, a system is built with applying 2 methods of cryptography, encryption and secret sharing to ensure data. Data that is ensured will be store at 2 different type of media storage namely cloud storage and laptop's internal storage. The test shows all the security functions work well.